Conversations about Bolívar through the pages of Repertorio Americano - Morales Méndez, Juan Andrey (2021)
This essay represents a journey through the pages of the magazine Repertorio Americano, and is inspired by texts dedicated to the figure of Simón Bolívar, published between January and April 1930. This exploration becomes a conversation that seeks to show the human part of the legend and coverspoetic and biographical portraits, learning in stages of his life, chronicles of his own words, and comparisons with magnificent beings like Don Quijote de la Mancha.